Educating a model based on explaining the relationships between Jihadi Management and General Policie - Hussein Zein al-Salehin (Universidad de Cienfuegos, 2020)
The purpose of this research is to teach a model based on the explanation of the relationships between the jihadist administration and general policies. Accordingly, the components of jihadist policymaking and management in the Iranian Civil Registry organization were taught through exploratory studies and knowledgeable expert surveys using the Delphi technique, and then these factors were tested in the form of the model designed in the statistical population. The population to test the model was 30 experts and the opinions of 148 managers of the Iranian organization for the Civil Registry were used to measure the variables. This research is descriptive-correlational, carried out from surveys. The data collection method in this research is a combination of library and field studies. The data collection tool is a questionnaire in which five questionnaires were used and the validity and reliability of the questionnaires were confirmed. Confirmatory factor analysis, structural equation modeling, and a sample t-test were used to analyze the data. The results of the study showed that there is a positive and significant relationship between the belief dimension of jihadist management and its components and the general policies of Iranian organization for civil registration. Furthermore, there is a positive and significant relationship between the functional dimension of jihadist management, its components, and the general policies in Iran for the Civil Registry.